Adaptation to anemia in hemoglobin E-ß thalassemia. - Allen, A; Fisher, C; Premawardhena, A; Peto, T; Allen, S; Arambepola, M; Thayalsutha, V; Olivieri, N; Weatherall, D (2010)
Hemoglobin E β thalassemia is the commonest form of severe thalassemia in many Asian countries. Its remarkably variable clinical phenotype presents a major challenge to determining its most appropriate management. In particular, it is not clear why some patients with this condition can develop and function well at very low hemoglobin levels. Here, we demonstrate that patients with hemoglobin Eβ thalassemia have a significant decrease in the oxygen affinity of their hemoglobin, that is an increased P(50) value, in response to anemia. This may in part reflect the lower level of hemoglobin F in this condition compared with other forms of β thalassemia intermedia. The ability to right-shift the oxygen dissociation curve was retained across the spectrum of mild and severe phenotypes, despite the significantly higher levels of hemoglobin F in the former, suggesting that efforts directed at producing a modest increase in the level of hemoglobin F in symptomatic patients with this disease should be of therapeutic value.